Diseño de un sistema de explotación para la extracción de materiales de construcción en el área de libre aprovechamiento “Río Chicaña”, con código 50000926, ubicada en el cantón Yantzaza, provincia de Zamora Chinchipe - Torres Masache, Jaime Alexander (2024)
The present degree project has been carried out with the objective of designing an exploitation system in the area of free use “Rio Chicaña” with code 50000926, located in the canton Yantzaza, province of Zamora Chinchipe, which is constituted by an area of 24 contiguous hectares. In order to carry out an adequate exploitation system for the extraction of stone materials, a sequence of objectives was projected with the purpose of achieving an optimal and technical design. Firstly, a topographic and geological characterization of the free use area was made with the help of a bibliographic review, followed by a survey of geological and topographic information in the field, reaching the conclusion that the study area consists of an irregular relief, this is because the Chicaña river crosses from north to south the mining area, geologically it is in an alluvial deposit belonging to the Quaternary period for the most part. The volume and quality of the aggregate and stone material in the study area was determined, resulting in an area of free use with a volume of 340234.91 m3 of material, which is of good quality and can be used for base and sub-base layers. The current processes and activities are detailed, as well as the daily production achieved in the current state, in addition to the technical description and performance of the machinery in the area of free use. For the selection of the exploitation system, three alternatives were proposed that could be implemented in the free use area, according to topographic criteria, flow, machinery, available infrastructure, geomorphology, material reserves, etc. The method chosen was open pit, using the gravel pit system by means of transversal dams, which is the most appropriate for extracting material in the area of free use “Rio Chicaña. To conclude and achieve the main objective of this work, the activities to be developed to implement the design that allows the efficient extraction of construction materials with the help of machinery and infrastructure were detailed and schematized. Key Words: Exploitation system, building material, arid and stony, free use, design